Invasive Pneumococcal Disease in High-risk Children: A 10-Year Retrospective Study. Issue 1 (18th November 2022) - van Warmerdam, Jacqui; Campigotto, Aaron; Bitnun, Ari; MacDougall, Georgina; Kirby-Allen, Melanie; Papsin, Blake; McGeer, Allison; Allen, Upton; Morris, Shaun K.
Abstract : Background: Despite the availability of conjugate pneumococcal vaccines, children with high-risk conditions remain vulnerable to invasive pneumococcal disease (IPD). This study sought to describe IPD prevalence, vaccination and outcomes among high-risk children. Methods: We used International Classification of Disease10 discharge and microbiology codes to identify patients hospitalized for IPD at a large pediatric hospital from January 1, 2009, to December 31, 2018. Patients were considered high-risk if they had: primary immunodeficiency, asplenia, transplant, active malignancy, sickle cell disease, cochlear implant, nephrotic syndrome, chronic lung disease, cerebrospinal fluid leak, HIV or used immunosuppressive therapy. Results: In total 94 high-risk patients were hospitalized for IPD. The most common high-risk conditions included malignancy (n = 33, 35%), solid-organ or bone marrow transplant (n = 17, 18%) and sickle cell disease (n = 14, 15%). Bacteremia was the most common presentation (n = 81, 86%) followed by pneumonia (n = 23, 25%) and meningitis (n = 9, 10%). No deaths occurred. Of 66 patients with known pneumococcal vaccination status, 15 (23%) were unvaccinated, and 51 (77%) received at least one dose of a pneumococcal vaccine; 20 received all four recommended pneumococcal conjugate vaccine (PCV) doses. Only three children received PPSV23. Of 20 children with no or partial (<3 doses) immunization, 70% (14) of IPD episodes were due to vaccine-preventable serotypes. Of 66 known IPD serotypes, 17% (n = 11) were covered by PCV13, 39% (n = 26) were covered by PPSV23 and 39% (n = 26) were nonvaccine serotype. Conclusions: Despite the availability of effective pneumococcal vaccines, IPD persists among children with high-risk conditions. Improving PCV13 and PPSV23 vaccination could significantly reduce IPD; most episodes were due to vaccine-preventable serotypes in incompletely immunized patients.